Nilai Ekonomi Pemanfaatan Hasil Hutan Bukan Kayu Di Taman Nasional Tesso Nilo Oleh Masyarakat Desa Lubuk Kembang Bunga Kabupaten Pelalawan, Provinsi Riau - Pebriandi; Lefdi Agung Nugraha; Defri Yoza; Yossi Oktorini; Muhammad Mardhiansyah; Ewi Irfani; Sonia Somadona; Evi Sribudiani; Feny Oktaningsih; Ika Lestari Hutasuhut (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2026)
Tesso Nilo National Park (TNNP) is one of the national parks in the province of Riau. TNNP is also one of the national parks that has great potential such as protected animals both Sumatran Elephants, Sumatran Tigers, HHK, and NTFPs. The existence of the forest is very important for the survival of the people living around the forest as well as the animals living in it. The diversity of types of forest products, especially NTFPs in the TNNP, are used by the people around the National Park, especially the people of Lubuk Kembang Bunga Village The use of NTFPs from national parks for both domestic needs and economic needs has different types and types, NTFPs used by the community, such as rattan, resin, honey, pandan and medicine from forest areas.